2007
DOI: 10.1603/0022-2585(2007)44[126:poecra]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <I>Ehrlichia canis</I> (Rickettsiales: Anaplasmataceae) in Dogs and <I>Rhipicephalus sanguineus</I> (Acari: Ixodidae) Ticks from Brazil

Abstract: The current study evaluated the prevalence of Ehrlichia canis Donatien and Lestoquard in domestic dogs, Canis familiaris L., and Rhipicephalus sanguineus (Latreille) (Acari: Ixodidae) ticks from different areas of Brazil. In Monte Negro County (state of Rondônia, Brazilian western Amazon), the indirect immunofluorescence assay detected E. canis-reactive antibodies (titer > or = 40) in 58/153 (37.9%) and 40/161 (24.8%) dogs from the urban and rural areas, respectively. These values were significantly different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
24

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 21 publications
6
39
0
24
Order By: Relevance
“…In the Monte Negro district of the State of Roraima, utilizing a randomly-selected sample of the urban area, Aguiar et al (2007b) obtained a prevalence rate of 37.9% (58/153) similar to the one observed in the present study. In another study, conducted by Carlos et al (2007) in two cities in the Southwestern region of the State of Bahia, Itabuna and Ilhéus, the infection rate was 36% (72/200), also similar to that of the present study; it should be noted, however, that the dogs in the study by Carlos et al were chosen from animals receiving clinical care.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the Monte Negro district of the State of Roraima, utilizing a randomly-selected sample of the urban area, Aguiar et al (2007b) obtained a prevalence rate of 37.9% (58/153) similar to the one observed in the present study. In another study, conducted by Carlos et al (2007) in two cities in the Southwestern region of the State of Bahia, Itabuna and Ilhéus, the infection rate was 36% (72/200), also similar to that of the present study; it should be noted, however, that the dogs in the study by Carlos et al were chosen from animals receiving clinical care.…”
Section: Discussionsupporting
confidence: 86%
“…There are scarce data available regarding E. canis infection in R. sanguineus (MURPHY et al, 1998;UNVER et al, 2001;NDIP et al, 2007). In the study performed by Aguiar et al (2007b) in Monte Negro (State of Rondônia) and São Paulo (State of São Paulo), E. canis-infection rates in R. sanguineus ticks varied from 2.4 (4/165) to 6.2% (10/162). Results similar to those obtained in the present study were observed in Africa, where the infection rate was 21% (19/92), with the tick specimens examined having been collected from 15 dogs (NDIP et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular methods demonstrated similar results for the effects of sex and age relative to infection by E. canis in Cuiaba, State of Mato Grosso (SILVA et al, 2010), and Ilheus and Itabuna, State of Bahia (CARVALHO et al, 2008). This pattern was also observed with serological assessments performed in several Brazilian cities: Cuiaba, State of Mato Grosso (SILVA et al, 2010), Monte Negro, State of Rondonia (AGUIAR et al, 2007), Patos, State of Paraiba (AZEVEDO et al, 2011), and southern cities in the State of Rio Grande do Sul (SAITO et al, 2008). Serological surveys made in the USA (RODGERS et al, 1989), Israel (HARRUS et al, 1997, and Japan (INOKUMA et al, 1999) revealed similar findings.…”
Section: Resultssupporting
confidence: 69%
“…Anti-Ehrlichia spp. antibodies were evaluated using the São Paulo strain of E. canis with a cut-off point at an initial dilution of 1:40 (AGUIAR et al, 2007). Anti-Rickettsia spp.…”
Section: Methodsmentioning
confidence: 99%